Considering Health Criminal Law: The Intersection Between Medical Ethics and Social Morality - Cahyaningrum, Luh Made Ari; Darma, I Made Wirya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Health criminal law in Indonesia is part of the legal system which aims to protect the public from medical practices that violate the law or endanger health, as well as an effort to maintain professionalism in health.  Several examples of cases that violate health criminal law in Indonesia often occur, such as medical malpractice, illegal abortion, and illegal organ and drug trafficking. Therefore, medical personnel are expected to act in accordance with professional ethical standards and respect patient rights, as well as be responsible for medical decision making. Overall, health criminal law in Indonesia has an important role in ensuring protection for patients and maintaining professional standards for medical personnel. However, regulatory challenges and the intersection between medical ethics and social morality often become obstacles to its implementation, requiring policies that are more responsive and balanced to the needs of society and medical personnel.